Faktor-Faktor yang Berhubungan dengan Kualitas Diet Remaja di SMA Yadika 12 Depok: Factors Related to Diet Quality in Adolescent at Yadika 12 High School Depok - Hidayat, Zahra Fadhlina; Marjan, Avliya Quratul; Wahyuningsih, Utami (Amerta Nutrition, 2024)
Background: Adolescents, a group with high nutritional needs, are facing the triple burden of malnutrition. Depok has the highest prevalence of overweight adolescents in Indonesia. Data shows an increase in the consumption of high-fat and high-sodium foods. Technological advancements have made foods more accessible, in 2020 Indonesia had the highest food delivery service usage in Southeast Asia. These factors may negatively impact adolescent diet quality, leading to health issues and higher risks of degenerative diseases. Objectives: This study analyzes the factors related to diet quality among adolescents at Yadika 12 High School Depok. Methods: This quantitative study used a cross-sectional design conducted at Yadika 12 High School Depok with 108 respondents selected using stratified random sampling. The dependent variable was diet quality, while the independent variables included the frequency of food delivery services usage, high-risk consumption habits, and nutrition knowledge. Diet quality was measured using the Diet Quality Index for Adolescents (DQI-A). Other variables were assessed using questionnaires and a Food Frequency Questionnaire. Bivariate analysis performed using the Spearman test. Results: Bivariate analysis indicated that the frequency of food delivery services usage (r=-0.044, p-value=0.654) is not associated with diet quality. In contrast, high-risk consumption habits (r=-0.256, p-value=0.007) and nutritional knowledge (r=0.217, p-value=0.024) associated with diet quality. Conclusions: High-risk consumption habits and nutrition knowledge are factors related to the diet quality of adolescents at Yadika 12 High School Depok. Interventions and implementing balanced nutrition guidelines and other nutritional information can be effective steps to improve the diet quality of adolescents.